To be or not to be a systems thinker: Do professional characteristics influence how students acquire systems-thinking skills? - Miller, Anat Nissel; Kordova, Sigal; Grinshpoun, Tal; Shoval, Shraga (Frontiers in Education, 2023)
The increased need for systems thinking has also created a growing need to detect systems thinkers. Systems thinkers grasp a system as one whole made up of interacting elements. They determine what affects the system by applying their ability to identify and understand the interrelationships between the system’s components and their impact on each other and on the system as a whole. This article investigates the factors influencing a person’s inclination to become a systems thinker. Four different groups had the same systems-thinking learning process. The four groups: working engineering students, full-time engineering students, social workers, and technological college faculty members differ in employment, professional skills, degree of familiarity with their working environment, and position in the organizational hierarchy. The participants completed a questionnaire to assess their systems-thinking capabilities before and after the learning process The questionnaire detected changes in their systems-thinking abilities following this learning and highlighted differences between the groups. The results show that various systems thinking aspects changed in each group following the learning process in a way linked with its different characteristics. Knowing that the diverse characteristics of different groups influence their ability to become systems thinkers enables designing systems thinking training programs adjusted to the characteristics of various groups.